2015
DOI: 10.1136/bmjopen-2015-007733
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory clinical trial of combination wound therapy with a gelatin sheet and platelet-rich plasma in patients with chronic skin ulcers: study protocol

Abstract: IntroductionChronic skin ulcers, such as diabetic ulcers, venous leg ulcers and pressure ulcers, are intractable and increasing in prevalence, representing a costly problem in healthcare. We developed a combination therapy with a gelatin sheet, capable of providing sustained release of platelet-rich plasma (PRP). The objective of this study is to investigate the safety and efficacy of autologous PRP covered with a hydrocolloid dressing and PRP covered with a gelatin sheet in the treatment of chronic skin ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
(24 reference statements)
0
41
0
1
Order By: Relevance
“…70 In Japan, human recombinant basic fibroblast growth factor (bFGF) (Kaken Pharmaceutical, Tokyo, Japan) is in use since 2001. bFGF stimulates fibroblasts and blood vessel formation. 71,72 Several studies have shown the effectiveness of recombinant human epidermal growth factor (rhEGF) in both diabetic foot ulcers and venous chronic wounds.…”
Section: Growth Factors and Other Mediatorsmentioning
confidence: 99%
“…70 In Japan, human recombinant basic fibroblast growth factor (bFGF) (Kaken Pharmaceutical, Tokyo, Japan) is in use since 2001. bFGF stimulates fibroblasts and blood vessel formation. 71,72 Several studies have shown the effectiveness of recombinant human epidermal growth factor (rhEGF) in both diabetic foot ulcers and venous chronic wounds.…”
Section: Growth Factors and Other Mediatorsmentioning
confidence: 99%
“…The other important signaling molecule produced by both keratinocytes and fibroblasts is TGF-β. Its expression induces the formation of granulation tissue, reepithelization and tissue reconstruction [5].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this artificial dermis was developed for use in various indications. Growth factor was loaded into the inner layer, which can accelerate chronic wound healing and prolong its stability [12,13]. The artificial dermis is impregnated with an antibiotic for application on contaminated wounds [14].…”
Section: Discussionmentioning
confidence: 99%